Challenges in Data Linkage – Experiences from An Upper Gastrointestinal Cancer Data Linkage Study - Nadia N Khan (International Journal of Population Data Science, 2020)
Introduction Nearly one quarter of a million Australian workers experience a work injury annually and make a benefit claim through one of the nation’s eleven workers’ compensation (WC) systems. The total cost to Australian society has most recently been estimated at $61.8 billion or 4.1% of GDP. The disaggregation of legislative responsibility between jurisdictions has contributed to a lack of common data standards, and thus minimal understanding of the efficiency or effectiveness of service provision in the Australian WC sector.